Importance of Language Laboratory in Developing Language Skills - Devina Krishna (Masyarakat Linguistik Indonesia Universitas Andalas, 2021)
The present paper deals with the importance of language laboratory in developing language skills. It basically presents how language labs are useful in developing language skills of the learners. Apart from the classroom lectures that students attend, the practical classes held in language labs hone their ability to comprehend language in a better manner. The present paper discusses the importance of these labs, benefits the receivers receive and why there is an urgent need for more such labs in academic institutions.